New lifestyles in old age : health, identity and well-being in Berryhill Retirement Village - Bernard, Miriam (Policy Press, 2004)
This report explores what it is like to live and work in the new Berryhill Retirement Village in Stoke-on-Trent (developed by The ExtraCare Charitable Trust and Touchstone Housing Association), and shows that retirement housing does not have to be planned and developed solely with middle-class professionals in mind.